The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21873/anticanres.12118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CpG Sites of SERPINA5 Promoter with Opposite Methylation Patterns in Benign and Malignant Prostate Cells

Abstract: Novel methylation patterns of two distinct CpG sites of the SERPINA5 promoter may be useful for differentiating benign from malignant prostate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…SERPINA5 is an important component of the SERPIN family known as a putative tumour suppressor gene [77]. It inhibits the activation of PSA and kallikrein, and it boosts sperm motility and fertilization in many studies [78]. The decreased expression of SERPINA5 seen in our discovery cohort and elevated PSA levels in newly diagnosed PCa patients compared with healthy individuals fits well with current research.…”
Section: Discussionsupporting
confidence: 87%
“…SERPINA5 is an important component of the SERPIN family known as a putative tumour suppressor gene [77]. It inhibits the activation of PSA and kallikrein, and it boosts sperm motility and fertilization in many studies [78]. The decreased expression of SERPINA5 seen in our discovery cohort and elevated PSA levels in newly diagnosed PCa patients compared with healthy individuals fits well with current research.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we found that SERPINA5 expression was significantly correlated with OS and RFS in LGG patients, and SERPINA5 high expression indicated patients with worse survival. More recently, researchers have found that the high methylation degree of CpG sites significantly correlated with lower SERPINA5 expression levels and two distinct CpG sites of the SERPINA5 promoter were hypermethylated in normal epithelial prostate cells, benign hyperplasic cells and low-invasive malignant LNCaP cells, whereas essentially unmethylated in aggressive DU-145 and PC-3 cell line (Hagelgans et al, 2017). In addition, SERPINA5 has been identified to be more highly methylated in HR-, basal-like, or p53 mutant breast cancer than HR+, luminal A, or p53 wild-type breast cancers, and gene signature composed of SERPINA5 and 3 other genes can predict the prognosis of patients with stage I LUAD (Conway et al, 2014;Luo, Wang & Zhang, 2018).…”
Section: Discussionmentioning
confidence: 99%